Cost-effectiveness analysis of camrelizumab plus chemotherapy as first-line treatment for advanced squamous NSCLC in China - Shao, Taihang; Ren, Yinan; Zhao, Mingye; Tang, Wenxi (Frontiers in Public Health, 2022)
Abstract Objective: Results of CameL-sq has revealed the clinical benefits to patients with advanced squamous non-small-cell lung cancer (sq-NSCLC). This study aims to evaluate the cost-effectiveness of camrelizumab plus chemotherapy to treat sq-NSCLC from the perspective of Chinese health care system. Methods: We used a partitioned survival model with lifetime horizon to evaluate the cost-effectiveness of camrelizumab plus chemotherapy vs. chemotherapy in treating sq-NSCLC. Baseline characteristics of patients and key clinical data were extracted from CameL-sq. Costs and utilities were collected from open-access database and published literature. Costs, quality-adjusted life-years (QALYs), life-years gained, incremental cost-effectiveness ratios (ICER) were chosen as economic outcome indicators. We also performed sensitivity analysis, subgroup analysis and scenario analysis to verify the stability of the basic-analysis results explore the results under different scenarios. Results: Combination therapy added 0.47 QALYS and 0.91 life-years with an incremental cost of 6347.81 compared with chemotherapy, which had an ICER of 13,572 per QALY. The probabilistic sensitivity analysis indicated that camrelizumab plus chemotherapy had a 37.8% probability of cost-effectiveness at a willingness-to-pay threshold (WTP) of 1 time GDP per capital. When WTP was set as 3 times GDP per capital, combination therapy had significant cost-effectiveness. Deterministic sensitivity analysis showed that cost of best supportive care was the factor with the greatest influence. The subgroup analysis found that combination therapy was associated with cost-effectiveness in several subgroups, including patients with disease stage ⅢB/ⅢC and with PD-L1 tumour proportion score ≤ 1%. Scenario analysis showed that ICER was positively correlated with the price of camrelizumab. Conclusion: In this economic evaluation, camrelizumab plus chemotherapy was unlikely to be cost-effective compared with chemotherapy in the first line therapy of sq-NSCLC from a perspective of Chinese health care system. Reducing the price of camrelizumab and tailoring treatments based on individual patient factors might improve the cost-effectiveness. Our findings may provide evidence for clinicians in making optimal decisions in general clinical practice.